Hand‐assisted laparoscopic transhiatal esophagectomy with a systematic procedure for en bloc infracarinal lymph node dissection. Issue 2 (9th December 2014) - Fujiwara, H.; Shiozaki, A.; Konishi, H.; Komatsu, S.; Kubota, T.; Ichikawa, D.; Okamoto, K.; Morimura, R.; Murayama, Y.; Kuriu, Y.; Ikoma, H.; Nakanishi, M.; et al.
Summary: Laparoscopic transhiatal esophagectomy is a minimally invasive approach for esophageal cancer. However, a transhiatal procedure has not yet been established for en bloc mediastinal dissection. The purpose of this study was to present our novel procedure, hand‐assisted laparoscopic transhiatal esophagectomy, with a systematic procedure for en bloc mediastinal dissection. The perioperative outcomes of patients who underwent this procedure were retrospectively analyzed. Transhiatal subtotal mobilization of the thoracic esophagus with en bloc lymph node dissection distally from the carina was performed according to a standardized procedure using a hand‐assisted laparoscopic technique, in which the operator used a long sealing device under appropriate expansion of the operative field by hand assistance and long retractors. The thoracoscopic procedure was performed for upper mediastinal dissection following esophageal resection and retrosternal stomach roll reconstruction, and was avoided based on the nodal status and operative risk. A total of 57 patients underwent surgery between January 2012 and June 2013, and the transthoracic procedure was performed on 34 of these patients. In groups with and without the transthoracic procedure, total operation times were 370 and 216 minutes, blood losses were 238 and 139 mL, and the numbers of retrieved nodes were 39 and 24, respectively. R0 resection rates were similar between the groups. The incidence of recurrent laryngeal nerve palsy was significantly higher in the group with the transthoracic procedure, whereas no significant differences were observed in that of pneumonia between these groups. The hand‐assisted laparoscopic transhiatal method, which is characterized by a systematic procedure for en bloc mediastinal dissection supported by hand and long device use, was safe and feasible for minimally invasive esophagectomy.